The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/anie.202111388
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Itaconation of Complex Peptides by Photoredox Catalysis

Abstract: Site-selective peptide functionalization provides astraightforwardand cost-effective access to diversify peptides for biological studies.A mong many existing non-invasive peptide conjugations methodologies,p hotoredoxc atalysis has emerged as one of the powerfula pproaches for site-specific manipulation on native peptides.Herein, we report ahighly Ntermini-specific method to rapidly access itaconated peptides and their derivatives through acombination of transamination and photoredox conditions.T his strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 140 publications
1
19
0
Order By: Relevance
“…To elucidate the mechanism of this reaction, Stern–Volmer experiments of 4CzIPN in relation to carbamoyl-DHP 2a (Scheme a) were examined, which indicated that carbamoyl-DHP 2a effectively quenched the luminescence property of 4CzIPN. This result suggested that the process was involved in a radical pathway, which was consistent with previous works. ,, As shown in Scheme b, we propose that this reaction proceeds possibly via a radical mechanism. First, photoexcitation of the 4CzIPN (E 1/2 (4CzIPN*/4CzIPNC •– ) = +1.43 V versus SCE in MeCN) forms an oxidant strong enough to take an electron from the dihydropyridine radical precursor 2 , generating an excited RNHCO-DHP radical cation A .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…To elucidate the mechanism of this reaction, Stern–Volmer experiments of 4CzIPN in relation to carbamoyl-DHP 2a (Scheme a) were examined, which indicated that carbamoyl-DHP 2a effectively quenched the luminescence property of 4CzIPN. This result suggested that the process was involved in a radical pathway, which was consistent with previous works. ,, As shown in Scheme b, we propose that this reaction proceeds possibly via a radical mechanism. First, photoexcitation of the 4CzIPN (E 1/2 (4CzIPN*/4CzIPNC •– ) = +1.43 V versus SCE in MeCN) forms an oxidant strong enough to take an electron from the dihydropyridine radical precursor 2 , generating an excited RNHCO-DHP radical cation A .…”
Section: Resultssupporting
confidence: 92%
“…This result suggested that the process was involved in a radical pathway, which was consistent with previous works. 20,25,26 As shown in Scheme 4b, we propose that this reaction proceeds possibly via a radical mechanism. First, photoexcitation of the 4CzIPN (E 1/2 (4CzIPN*/4CzIPNC •− ) = +1.43 V versus SCE in MeCN) 27 forms an oxidant strong enough to take an electron from the dihydropyridine radical precursor 2, generating an excited RNHCO-DHP radical cation A.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Very recently, Wang and co-workers, inspired by the noteworthy importance of itaconate and its derivatives in the immune metabolism of inflammation and tumor via cysteine–protein conjugation via Michael reactions, developed a site-selective synthesis of N-terminal itaconated peptides 31 through the photocatalytic coupling of 2-(bromomethyl)acrylate 30 with peptidic carbamoyl-radicals (Scheme 17). 80 Throughout the optimization studies, it was found that Iridium catalyst PC5 showed the best performance, and CFL irradiation afforded better yields than blue LED irradiation, in a very short reaction time (30 min). Regarding the scope, a set of peptide-carbamoyl-DHPs 29 , synthesized using SPPS (Solid Phase Peptide Synthesis), bearing photolabile residues (such as Trp and Met), could be selectively coupled to 30 , affording a family of peptide itaconamides 31 in good to excellent yields.…”
Section: Generation Of Carbamoyl Radical From 4-substituted-14-dihydr...mentioning
confidence: 98%
“…(Our lab and others have found that some peptides are readily degraded with higher energy <450 nm light) [18] . By operating through SET reduction, organic dyes are also less likely to cause undesirable side reactions on peptides, which generally have amino acids that can be oxidatively modified, including Tyr, [19] Trp, [20] Met, [21, 22] His, [23, 24] N‐termini, [25] and C‐termini [26] . The discovery of an organic dye that can facilitate c NP synthesis would not only provide ready access to a novel biopharmaceutical modality but bolster the utility of fluorescent organic dyes for biomolecular synthesis.…”
Section: Introductionmentioning
confidence: 98%